Functional outcome of medial patella femoral ligament reconstruction: a prospective study of novel hamstring sparing technique without patella anchors - Mohan, Jithin; Jacob, Nithisha Mary; John, John Thayyil; P., Akshay; Salam, Shinas B.; Pillai, Abhilash (International Journal of Research in Orthopaedics, 2025)
Background: A composite graft made of medial retinaculum and quadriceps tendon can be used instead of hamstring graft for medial patellofemoral reconstruction in recurrent dislocation of patella. Our study aims at determining the functional outcome of MPFL reconstruction with this composite graft. Methods: This is a unicentric, prospective observational study conducted in 60 patients with recurrent dislocation of patella with normal Q angle and without trochlear dysplasia. A composite graft composed of medial patella retinaculum and quadriceps was harvested, one end was sutured at medial superior 2/3rd junction of patella with ethibond. The other end of graft fixed at schottles point with a bio screw. Patients were followed up at 6 weeks, 3 months, 6 months and then yearly. A preoperative and post operative Lysholm score and Kujala score were used for comparison. Results: There was a significant improvement in Kujala and Lysholm scores. Only 3 out of 60 patients developed further instability that was managed non surgically. There was no statistically significant association with ligamentous laxity and the outcome. Conclusion: Considering the donor site morbidity and patella fracture this novel hamstring sparing MPFL reconstruction is superior, and outcomes are comparable with previous techniques.